2021
DOI: 10.1111/bph.15450
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical rodent models of cardiac fibrosis

Abstract: Cardiac fibrosis (scarring), characterised by an increased deposition of extracellular matrix (ECM) proteins, is a hallmark of most types of cardiovascular disease and plays an essential role in heart failure progression. Inhibition of cardiac fibrosis could improve outcomes in patients with cardiovascular diseases and particularly heart failure. However, pharmacological treatment of the ECM build‐up is still lacking. In this context, preclinical models of heart disease are important tools for understanding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 157 publications
0
2
0
Order By: Relevance
“…A large number of experimental studies have shown that in animal models of systemic hypertension (eg, spontaneous genetic hypertension, renovascular, exogenous induction, and transgenic models) adverse LV remodeling and MIF begin after elevation in BP and both progress in parallel thereafter (Figure 2). 36,37 Mechanical stress that occurs due to hypertension-induced LV pressure overload can be sensed by resident cardiac fibroblasts by cell surface receptors (eg, integrins and discoidin domain receptors) 38 that mediate mechanotransduction signaling involved in fibroblast activation, as well as differentiation into myofibroblasts. Moreover, the extracellular matrix functions as a reservoir of profibrotic signaling molecules that can be released upon mechanical stress.…”
Section: Myocardial Fibrosis In Hhdmentioning
confidence: 99%
“…A large number of experimental studies have shown that in animal models of systemic hypertension (eg, spontaneous genetic hypertension, renovascular, exogenous induction, and transgenic models) adverse LV remodeling and MIF begin after elevation in BP and both progress in parallel thereafter (Figure 2). 36,37 Mechanical stress that occurs due to hypertension-induced LV pressure overload can be sensed by resident cardiac fibroblasts by cell surface receptors (eg, integrins and discoidin domain receptors) 38 that mediate mechanotransduction signaling involved in fibroblast activation, as well as differentiation into myofibroblasts. Moreover, the extracellular matrix functions as a reservoir of profibrotic signaling molecules that can be released upon mechanical stress.…”
Section: Myocardial Fibrosis In Hhdmentioning
confidence: 99%
“…In MI-induced HF, there is a reparative response to acute ischemic injury since the latter induces cardiomyocyte death. Under these circumstances, there is an acute inflammatory phase to remove necrotic tissue followed by increased collagen production to stabilize cardiac structural integrity at the site of MI injury, although this profibrotic activity often spills into regions remote from the initial injury (Prabhu and Frangogiannis, 2016;Wang et al, 2022). In contrast, in hypertensive heart disease with no obvious acute injury, there is persistent inflammation and oxidative stress that leads to ECM buildup throughout the heart (Berk et al, 2007).…”
Section: B Heartmentioning
confidence: 99%
“…In contrast, in hypertensive heart disease with no obvious acute injury, there is persistent inflammation and oxidative stress that leads to ECM buildup throughout the heart (Berk et al, 2007). This is exemplified in various reactive cardiac fibrosis models, as recently reviewed (Wang et al, 2022). This so-called reactive fibrosis does not usually have a defining trigger and is a common sequela in hypertension and cardiometabolic disease.…”
Section: B Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, detection of ISPT in a pharmaceutical formulation or biological matrix is carried out using conventional techniques such as flow-injection analysis, spectroscopic methods, and nuclear magnetic resonance. Despite their effectiveness, these techniques are restricted to laboratory-scale measurements and require complicated chemical procedures that are often long and tedious . Furthermore, these approaches need a well-maintained infrastructure and are unsuitable for field applications.…”
Section: Introductionmentioning
confidence: 99%